Comunicação: uma abordagem sobre o ensino da língua portuguesa na educação profissional e tecnológica e a práxis docente - Souza, Eliza Silvana de (2019)
This dissertation has as general objective to discuss the teaching praxis in the teaching of the Portuguese Language for Labor. Then, three chapters, all connected to the teacher's performance, are presented. The first chapter shows the path of Brazilian Professional and Technological Education, from the decree of president Nilo Peçanha (1909) and, from the surveys carried out, it shows the paradigm shift of the modality. The second chapter brings the fundamentals of Organizational Communication, the basis for Professional Communication, which is understood as a curricular unit in the modality in focus. The third chapter, the core research, provides reflections on the curriculum constitution for the teaching of Professional Communication in Human Resources Technical Courses proposed by Centro Paula Souza, that as a curriculum component, should be taught considering the guiding documents as demanded of the current labor scenario and the specificities related to the classroom practice. In this last stage, besides a brief analysis about the curricular component, we present two qualitative and quantitative case studies elaborated with the intention of detailing the profile of the first module of the Human Resources Technician, class for which the didactic proposals were directed in the first semester of 2019, and the second study, aimed at employees, with the objective of diagnosing contemporary communicative needs in the labor context. Finally, practical approaches to teaching Portuguese Language for labor are presented, activities that celebrate practical approaches (ANTUNES, 2003, 2005 E 2007) promoted the teaching of the language to social apply and search for involving the teacher on the actions of studying and learning.